2013
DOI: 10.4236/ojpsych.2013.31a009
|View full text |Cite
|
Sign up to set email alerts
|

Threat perception predicts cognitive behavioral therapy outcomes in anxious children

Abstract: Objective: Anxiety disorders of childhood are prevalent, debilitating conditions that do not always respond to existing treatments. Attentional biases towards threatening stimuli have been reported in anxious children and hypothesized to interfere with treatment response. Therefore, we examined such biases in children with anxiety disorders in relation to cognitive behavioral therapy (CBT) outcomes. Method: Thirty-eight children diagnosed with anxiety disorders in a specialized clinic (21 girls and 17 boys; ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
(52 reference statements)
0
6
1
Order By: Relevance
“…Given that previous research into the effect of CBT on attentional bias in anxious children is limited, with two studies finding no effect of CBT on bias (Waters et al 2008a;Manassis et al 2013), the present study provides novel findings relating to this issue. Moreover, to our knowledge, no previous research has investigated whether attention control changes over the course of CBT in children with anxiety disorders.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Given that previous research into the effect of CBT on attentional bias in anxious children is limited, with two studies finding no effect of CBT on bias (Waters et al 2008a;Manassis et al 2013), the present study provides novel findings relating to this issue. Moreover, to our knowledge, no previous research has investigated whether attention control changes over the course of CBT in children with anxiety disorders.…”
Section: Discussionmentioning
confidence: 79%
“…Previous research into the effect of CBT on attentional bias is very limited. Waters et al (2008b) and Manassis et al (2013) found no effect of CBT on attentional bias in anxious children. Comparison of the present results with these studies is complicated by different experimental methods, as noted earlier.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Manassis and colleagues [35], however, found no treatment-related changes in a probe position task from pre-to post-CBT in anxious children. One study that may reconcile these findings examined attentional bias on a visual probe task, threat interpretation bias, and selection of avoidant solutions in the same children before and after CBT.…”
Section: Parents Of Anxious Children May Share Their Cognitive Biasesmentioning
confidence: 90%
“…Intervention with adolescents may need to respect developing executive functions (e.g., focus on hypothesistesting rather than reassuring statements), attend to social as well as physical threats, and involve families less in developing emotion regulation skills [34,35]. Legerstee and colleagues then provided a highly intensive form of CBT to non-responders, with improved treatment response [34].…”
Section: Parents Of Anxious Children May Share Their Cognitive Biasesmentioning
confidence: 99%